Novel chaotic oppositional fruit fly optimization algorithm for feature selection applied on COVID 19 patients' health prediction - Bacanin, Nebojsa; Budimirovic, Nebojsa; K, Venkatachalam; Strumberger, Ivana; Alrasheedi, Adel Fahad; Abouhawwash, Mohamed (PloS one, 2022)
The fast-growing quantity of information hinders the process of machine learning, making it computationally costly and with substandard results. Feature selection is a pre-processing method for obtaining the optimal subset of features in a data set. Optimization algorithms struggle to decrease the dimensionality while retaining accuracy in high-dimensional data set. This article proposes a novel chaotic opposition fruit fly optimization algorithm, an improved variation of the original fruit fly algorithm, advanced and adapted for binary optimization problems. The proposed algorithm is tested on ten unconstrained benchmark functions and evaluated on twenty-one standard datasets taken from the Univesity of California, Irvine repository and Arizona State University. Further, the presented algorithm is assessed on a coronavirus disease dataset, as well. The proposed method is then compared with several well-known feature selection algorithms on the same datasets. The results prove that the presented algorithm predominantly outperform other algorithms in selecting the most relevant features by decreasing the number of utilized features and improving classification accuracy.
Keywords: Arizona; Algorithms; strojové učení; Animals; Machine Learning; algoritmy; zvířata; Drosophila; COVID-19